Trisomy 13 and 18—Prevalence and mortality—A multi‐registry population based analysis. Issue 12 (30th September 2019) - Goel, Nitin; Morris, Joan K.; Tucker, David; de Walle, Hermien E. K.; Bakker, Marian K.; Kancherla, Vijaya; Marengo, Lisa; Canfield, Mark A.; Kallen, Karin; Lelong, Nathalie; Camelo, Jorge L.; Stallings, Erin B.; et al.
Abstract: The aim of the study is to determine the prevalence, outcomes, and survival (among live births [LB]), in pregnancies diagnosed with trisomy 13 (T13) and 18 (T18), by congenital anomaly register and region. Twenty‐four population‐ and hospital‐based birth defects surveillance registers from 18 countries, contributed data on T13 and T18 between 1974 and 2014 using a common data‐reporting protocol. The mean total birth prevalence (i.e., LB, stillbirths, and elective termination of pregnancy for fetal anomalies [ETOPFA]) in the registers with ETOPFA ( n = 15) for T13 was 1.68 (95% CI 1.3–2.06), and for T18 was 4.08 (95% CI 3.01–5.15), per 10, 000 births. The prevalence varied among the various registers. The mean prevalence among LB in all registers for T13 was 0.55 (95%CI 0.38–0.72), and for T18 was 1.07 (95% CI 0.77–1.38), per 10, 000 births. The median mortality in the first week of life was 48% for T13 and 42% for T18, across all registers, half of which occurred on the first day of life. Across 16 registers with complete 1‐year follow‐up, mortality in first year of life was 87% for T13 and 88% for T18. This study provides an international perspective on prevalence and mortality of T13 and T18. Overall outcomes and survival among LB were poor with about half of live born infants not surviving first week of life; nevertheless about 10% survived the first year of life. Prevalence and outcomes varied by country and termination policies. The study highlights the variation in screening, data collection, and reporting practices for these conditions.